Perceptions and Attitudes of Urban Muslim Youth towards Modernity and Globalization - Fitryansyah, Muhammad Andryan; Sofiyati (Pusat Pengkajian dan Pengembangan Islam Jakarta (PPIJ), 2024)
This research examines the perceptions and attitudes of urban Muslim youth in Indonesia towards modernity and globalization. Urban Muslim youth navigate the challenges and opportunities of a globalized world while striving to maintain their religious and cultural identities. This study aims to explore the factors influencing their perceptions, including religiosity, family dynamics, education, economic conditions, and technological advancements. Through a comprehensive literature review, this research highlights how these factors interplay to shape the worldview and behaviors of young Muslims in urban settings. The findings reveal that while some urban Muslim youth embrace modernity and globalization, seeing them as opportunities for technological advancement and improved quality of life, others perceive them as threats to their traditional values and religious identity. The study underscores the importance of understanding these perceptions to address the social and religious development of urban Muslim communities. By providing insights into the attitudes of urban Muslim youth, this research contributes to the broader discourse on religious and cultural identities amidst the forces of modernity and globalization.